A qualidade em serviços logísticos como um fator relevante para a lealdade do cliente Ecommerce - Barros, Fausto Karlaire de (2016)
Logistics service quality is of strategic importance in e-retail. However, it is not clear which of its elements are more relevant to the customer perceptions since logistics service quality measures have been developed mainly for B2B relationships. There